Design, comparison and analysis of low pass FIR filter using window techniques method. (2022) - Sulaiman, Ibrahim Abdulhadi; Hassan, Hussain Mohammad; Danish, Mohammad; Singh, Munendra; Singh, P.K.; Rajoriya, Manisha
Abstract: In digital communication, a filter is any device that selectively attenuates any unwanted component from a received signal. It essentially changes or reshapes the waveform of a signal in the desired manner. In this work, we have designed and studied low pass filter using Rectangular, Bartlett, Hamming, Hanning, Tukey and Kaiser Window algorithms and compared them with each other for further analysis. The parameters we used for designing the filter are sampling frequency, cut off frequency, filter order and a variable parameter, α. MATLAB toolbox for DSP, namely FDA Tool and FV Tool were employed for the realization of the design .